1998
DOI: 10.1086/517133
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Time to Sputum Conversion Among Patients with Smear‐Positive Pulmonary Tuberculosis

Abstract: This parent BCG strain was distributed widely, and the distributed and may have become further attenuated in the process [6].All BCG substrains share a 10-kb deletion (RD1), which may Although there is much to be learned by comparing substrains, a crucial question is whether any BCG substrain should be used in populations with high rates of both HIV infection and tuberculo- Factors Influencing Time to Sputum Conversion Among sis. We demonstrated a high mortality among patients with AIDS Patients with Smear-Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 1 publication
10
58
0
5
Order By: Relevance
“…Interestingly enough, this favorable effect was evident even when the experimental group had a higher proportion of patients with cavitary lesions and a trend to have more AFB in their initial sputum smear, two conditions that have been described to be associated with a prolonged time for sputum culture conversion. 30 Patients in the control group followed a clinical and bacteriologic evolution that was similar or better than the course already described in a number of studies. Thus, in our study the median time to obtain the first negative sputum culture result was 28 days, which was very similar to the 26 days found by Telzak et al 30 Likewise, the sputum culture result became negative in 73% of our patients after the first month of treatment, which was comparable to the 69% found by the British Medical Research Council.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Interestingly enough, this favorable effect was evident even when the experimental group had a higher proportion of patients with cavitary lesions and a trend to have more AFB in their initial sputum smear, two conditions that have been described to be associated with a prolonged time for sputum culture conversion. 30 Patients in the control group followed a clinical and bacteriologic evolution that was similar or better than the course already described in a number of studies. Thus, in our study the median time to obtain the first negative sputum culture result was 28 days, which was very similar to the 26 days found by Telzak et al 30 Likewise, the sputum culture result became negative in 73% of our patients after the first month of treatment, which was comparable to the 69% found by the British Medical Research Council.…”
Section: Discussionmentioning
confidence: 58%
“…30 Patients in the control group followed a clinical and bacteriologic evolution that was similar or better than the course already described in a number of studies. Thus, in our study the median time to obtain the first negative sputum culture result was 28 days, which was very similar to the 26 days found by Telzak et al 30 Likewise, the sputum culture result became negative in 73% of our patients after the first month of treatment, which was comparable to the 69% found by the British Medical Research Council. 31 Therefore, we can reasonably affirm that differences in the outcome between the groups were not due to a less-than-expected responsiveness of the control group.…”
Section: Discussionmentioning
confidence: 58%
“…Compared with the participants in the Karyadi et al study, our study participants were more likely at baseline to have higher-grade sputum smear positivity (36% 3+ compared with 7.5% 3+) and to have pulmonary cavities (73% compared with 37.5%) (18). Both of these factors are known to be associated with longer sputum smear and culture conversion times (33). However, our failure to find a benefit for the micronutrient intervention is in keeping with 2 other studies: a second Indonesian trial, as yet unpublished, found no improvement in sputum smear conversion with zinc and vitamin A (34), and a Tanzanian trial reported no effect of a multimicronutrient intervention or zinc on sputum culture conversion at 2 mo (21).…”
Section: Secondary Analysesmentioning
confidence: 52%
“…This may be due to either previously existing drug-resistant strains or the emergence of resistant strains due to the failure of systemic drugs to reach extensive cavitary disease in the lungs that contain numerous acid fast bacilli (AFB) (116). The same authors have shown that HIVpositive individuals converted to smear negative at a faster rate than HIV-negative patients.…”
Section: Complimentary With Oral and IVmentioning
confidence: 99%